Genetic variability of multifunctional HC-Pro gene of Lettuce mosaic virus in northern region of India - and RAJARSHI KUMAR GAUR*, RITESH MISHRA, RAKESH KUMAR VERMA (Indian Phytopathology, 2017)
Lettuce mosaic virus (LMV) is an economically important pathogen causing mosaic disease in lettuce like it causes in spinach (Spinacia oleracea). Isolates of LMV originating from different geographical regions in northern India were collected during the survey of 2013-2014. Lettuce mosaic virus (LMV) belongs to Potyviridae family (genus Potyvirus) and isÂ mainly transmitted by aphids. This study covered the genetic variability of Helper component proteinase (HC-Pro) gene of LMV isolates. HC-Pro is multifunctional activity gene, which helps in transmission of virus. The amplified PCR products of 1.3 kilo basepairs (kb) were obtained from five different isolates, sequenced and deposited in NCBI GenBank. Two isolates R4 and HR1 from Rajasthan (KJ558375, KM501033), isolate R5 from Haryana (KP635365), isolate R6 from Uttar Pradesh (KP635366) and isolate R4 from Delhi (KP635367)]. The phylogenetic analysis of LMV HC-Pro sequences is showed divergence with other isolates. These isolates showed two different clusters vis-a-vis diversity amongst each other.